Impact of major events on housing prices in Hangzhou based on regression discontinuity - Zhang, Ling; Zhu, Lifei; Yang, Linzun (International Journal of Strategic Property Management, 2022)
Based on the regression discontinuity method, housing transaction price data of Hangzhou at the community level were used to assess the impacts of a serious of major events on housing prices in Hangzhou. The results show that the 2008 financial crisis had the strongest negative impact on housing prices, with prices decreasing by about 20%. Winning the right to host the G20 summit did not significantly impact housing prices, while holding the summit caused an increase in prices (about 10%). The first implementation of the home purchase restriction (HPR) caused a decreasing discontinuity of housing prices. Cancellation of the HPR did not cause a discontinuity effect, but the trend changed from negative to positive, and resumption of the HPR for local residents yielded the largest drop in housing prices, resulting in a 10% downward cut-point. However, the impact time was relatively short and did not change the rapid rising trend of housing prices.